Novel considerations on EGFR-based therapy as a contributor to cancer cell death in NSCLC - Peng, Weiwei; Yao, Chengyun; Pan, Qin; Zhang, Zhi; Ye, Jinjun; Shen, Bo; Zhou, Guoren; Fang, Ying (Frontiers in Oncology, 2023)
Epidermal growth factor receptor (EGFR)-tyrosine kinase inhibitors (TKIs) represented by gefitinib and erlotinib are widely used in treating non-small cell lung cancer (NSCLC). However, acquired resistance to EGFR-TKI treatment remains a clinical challenge. In recent years, emerging research investigated in EGFR-TKI-based combination therapy regimens, and remarkable achievements have been reported. This article focuses on EGFR-TKI-based regimens, reviews the standard and novel application of EGFR targets, and summarizes the mechanisms of EGFR-TKI combinations including chemotherapy, anti-vascular endothelial growth factor monoclonal antibodies, and immunotherapy in the treatment of NSCLC. Additionally, we summarize clinical trials of EGFR-TKI-based combination therapy expanding indications to EGFR mutation-negative lung malignancies. Moreover, novel strategies are under research to explore new drugs with good biocompatibility. Nanoparticles encapsulating non-coding RNA and chemotherapy of new dosage forms drawn great attention and showed promising prospects in effective delivery and stable release. Overall, as the development of resistance to EGFR-TKIs treatment is inevitable in most of the cases, further research is needed to clarify the underlying mechanism of the resistance, and to evaluate and establish EGFR-TKI combination therapies to diversify the treatment landscape for NSCLC.